1997
DOI: 10.1089/neu.1997.14.15
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Quantification of Lesion Volume following Experimental Traumatic Brain Injury in the Rat

Abstract: A reliable and rapid method for quantifying lesion volume following traumatic brain injury (TBI) has vast potential in brain injury research. Staining with 2, 3, 5-triphenyltetrazolium chloride (TTC) provides for demarcation of damaged or infarcted tissue from normal, viable cerebral tissue, in which a red formazan product is formed by reduction during cellular respiration of mitochondrial dehydrogenase enzymes. The present study evaluated the use of TTC staining to quantify the cortical lesion volume in rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Vink et al (1990) found no injuryinduced changes in hemispheric cortical respiratory coupling after FP brain injury, although sustained bilateral hemispheric deficits have been reported after CCI brain injury in rats . This discrepancy between models may originate from the greater severity of injury induced by CCI than FP in terms of blood-brain barrier disruption and lesion volume (Perri et al, 1997;Hicks et al, 1997;Baskaya et al, 2000). However, in vitro mitochondrial function may be preserved despite morphologic damage to mitochondrial membranes (Vander Heiden et al, 2000;Waterhouse et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Vink et al (1990) found no injuryinduced changes in hemispheric cortical respiratory coupling after FP brain injury, although sustained bilateral hemispheric deficits have been reported after CCI brain injury in rats . This discrepancy between models may originate from the greater severity of injury induced by CCI than FP in terms of blood-brain barrier disruption and lesion volume (Perri et al, 1997;Hicks et al, 1997;Baskaya et al, 2000). However, in vitro mitochondrial function may be preserved despite morphologic damage to mitochondrial membranes (Vander Heiden et al, 2000;Waterhouse et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, brain tissue damaged by the FPI was unable to convert TTC and remained unstained (white color). The TTC staining technique is a useful, rapid, and reproducible method for quantitation of lesion volume in multiple models of focal cerebral damage, including FPI (Perri et al, 1997). After the color development, sections were washed in HBSS buffer, fixed in 10% formalin, and kept at 48C until pictures were recorded by a camera mounted to a dissecting microscope.…”
Section: Estimation Of Brain Lesion Volume After Tbimentioning
confidence: 99%
“…Cerebral energetic impairment can be assessed by non-invasive and invasive methods, including magnetic resonance (MR) spectroscopy 11 , regional bioluminescence imaging 12 , histology [triphenyl tetrazolium chloride (TTC)] 13 and cytochrome oxidase (CO) immunohistochemistry 14 , in vitro autoradiography 15,16 , in vitro analysis of mitochondrial respiratory coupling 6,17 and analysis of metabolites within the extracellular space by microdialysis 18 or in the cerebrospinal fluid 19 . These experimental in vitro and in vivo studies revealed partially reversible metabolic changes characterized by a strong regional and temporal heterogeneity.…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 99%